THEORETICAL ASPECTS OF STUDYING THE PSYCHOLOGICAL BASIS FOR THE FORMATION OF COMBAT READINESS IN SERVICEME OF THE LAND FORCES OF THE ARMED FORCES OF UKRAINE - Filonenko, Lesia (Personality and environmental issues, 2025)
The article reveals the essence of psychological readiness as a systemic construct that encompasses the motivational, volitional, emotional, and cognitive components of personality. It examines the relationship between psychological readiness and combat effectiveness. The structural components of readiness are identified as key elements such as motivational orientation toward task completion, emotional stability, stress resistance, level of self-control, operational thinking, and adaptive personal resources. The influence of the combat environment on the mental state of servicemen is analyzed. Particular attention is paid to psychological stressors that accompany the execution of tasks under life- and health-threatening conditions. The study also considers internal factors (individual traits, psychophysiological characteristics) and external factors (service organization, training level, moral and psychological support) that influence the formation of combat readiness. The role of military psychologists and command staff is highlighted in creating a favorable moral and psychological climate and enhancing the readiness of personnel — a contribution that is of crucial importance for the scientific and practical understanding of psycho-emotional preparation of the military, especially under the current conditions of Ukraine’s defense efforts.